The role of working experience moderating the effect of emotional intelligence, intellectual intelligence, and spiritual intelligence on the ethical decision of tax consultants in Bali area - Wiguna, I Putu Indra; Yadnyana, Ketut (International research journal of management, IT and social sciences, 2019)
This study aims to examine the effect of emotional intelligence, intellectual intelligence, and spiritual intelligence on ethical decisions of tax consultants with work experience as moderating variables. The population in this study were all registered tax consultants in the Bali Region who had practice licenses in accordance with the Directory of Indonesian Tax Consultants Association in 2018 as many as 58 people. The research sample was determined by purposive sampling method and based on the specified criteria obtained a total sample of 41 people. Research data was collected through survey methods with questionnaire techniques. The data analysis technique used in the study was multiple linear regression analysis and moderated regression analysis. The results showed that the variables of emotional intelligence had a positive effect on ethical decisions, intellectual intelligence had a positive effect on ethical decisions, and spiritual intelligence had a positive effect on ethical decisions. Work experience moderates the effect of emotional intelligence, intellectual intelligence, and spiritual intelligence on the ethical decisions of tax consultants.